2017
DOI: 10.1007/978-1-4939-7362-0_6
|View full text |Cite
|
Sign up to set email alerts
|

Hyper-SUMOylation of K+ Channels in Sudden Unexplained Death in Epilepsy: Isolation and Primary Culture of Dissociated Hippocampal Neurons from Newborn Mice for Subcellular Localization

Abstract: The physiological characteristics of rat and murine hippocampal neurons are widely studied, especially because of the involvement of the hippocampus in learning, memory, and neurological functions. Primary cultures of hippocampal neurons are commonly used to discover cellular and molecular mechanisms in neurobiology. By isolating and culturing individual hippocampal neurons, neuroscientists are able to investigate the activity of neurons at the individual cell and single synapse level, and to analyze propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…After seizures, SENP2‐deficient mice develop atrioventricular block and cardiac arrest. Seizures and heart block are prevented by an opener of the Kv7 channel 15,19,159 . Therefore, we revealed the pathogenic role of SUMOylation in the nervous system and established an animal model of SUDEP (sudden unexplained death in epilepsy).…”
Section: Channelopathymentioning
confidence: 99%
“…After seizures, SENP2‐deficient mice develop atrioventricular block and cardiac arrest. Seizures and heart block are prevented by an opener of the Kv7 channel 15,19,159 . Therefore, we revealed the pathogenic role of SUMOylation in the nervous system and established an animal model of SUDEP (sudden unexplained death in epilepsy).…”
Section: Channelopathymentioning
confidence: 99%
“…Isolation of rat primary hippocampal neurons was conducted according to the previous reports [17]. Specially, the newborn Sprague-Dawley rats at the age of 1–3 days were obtained from Liaoning Changsheng Biotechnology Co., Ltd. (Liaoning, China) for the gathering of hippocampal tissues.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, additional studies have shown that SUMOylation and its pathways are associated with human diseases (25)(26)(27)(28). Various types of stress induce the upregulated SUMOylation, making SUMOylation a critical mechanism to protect cells from stress-induced apoptosis or cell death (29,30).…”
Section: Sumoylationmentioning
confidence: 99%
“…(sudden unexplained death in epilepsy) patients (25)(26)(27). SENP2 has been reported to play a crucial role in hepatocellular carcinoma (HCC) cell growth by modulating b-catenin stability (68).…”
Section: Senp2mentioning
confidence: 99%